A 2Ma old baboon-like monkey from Northern Greece and new evidence to support the Paradolichopithecus – Procynocephalus synonymy (Primates: Cercopithecidae). Issue 121 (August 2018) - Kostopoulos, Dimitris S.; Guy, Franck; Kynigopoulou, Zoi; Koufos, George D.; Valentin, Xavier; Merceron, Gildas
Abstract: A new fossil cranium of a large papionin monkey from the Lower Pleistocene site of Dafnero-3 in Western Macedonia, Greece, is described by means of outer and inner morphological and metric traits using high-resolution micro-computed tomography. Comparisons with modern cercopithecids and contemporaneous Eurasian fossil taxa suggest that the new cranium could equally be ascribed to either the Eurasian Paradolichopithecus or to the East Asian Procynocephalus . The combination of the available direct and indirect fossil evidence, including the new cranium from Dafnero, revives an earlier hypothesis that considers these two sparsely documented genera as synonyms. The timing and possible causes of the rise and demise of Paradolichopithecus - Procynocephalus are discussed.